A Buddhist Contribution to Community Empowerment Models - Fany Amelia Sari; Ari Suryana; Kabri Kabri (CV. Rayyan Dwi Bharata, 2025)
This article proposes a novel integrative framework for community development that synthesizes Asset-Based Community Development (ABCD) with the ethical and philosophical underpinnings of Socially Engaged Buddhism (SEB). The study responds to two core theoretical critiques of ABCD: its inadequate treatment of intrinsic human motivation and its neglect of structural power dynamics. Employing a Systematic Literature Review (SLR) methodology, the research maps the conceptual foundations and criticisms of ABCD, explores key teachings of SEB and canonical Pāli texts, and identifies a research gap in integrating these paradigms. The resulting Social-Spiritual-Critical Empowerment Model incorporates Buddhist values such as compassion (karuṇā), interdependence (paṭiccasamuppāda), and distributive justice into the ABCD methodology. The model offers a multidimensional approach to empowerment, social, spiritual, and critical, that enables communities to mobilize internal assets, cultivate resilience, and engage in structural critique. This framework provides a theoretically grounded, ethically sustainable, and contextually adaptable model for holistic community development.